Clinico therapeutic management of brucellosis in Kashmir - PEER, F U; BHATTACHARYYA, H K; ANSARI, MD MOIN; GOSWAMI, P (The Indian Journal of Animal Reproduction, 2023)
Management of brucellosis in three cows and in. one human using oxytetracycline and Streptomycin combination has been recorded.
Keywords: Brucellosis; Animals; Human; Oxytetracycline; Streptomycin